Absence of cytomegalovirus, Epstein-Barr virus, and papillomavirus DNA from adenoma and adenocarcinoma of the colon - Boguszaková, L; Hirsch, I; Brichácek, B; Faltýn, J; Fric, P; Dvoráková, H; Vonka, V (Acta virologica, 1988)
Biopsy specimens from 13 patients with adenocarcinoma of the colon and from 10 patients with endoscopic polypectomies for colon adenoma were examined for the presence of the DNA of cytomegalovirus (CMV), Epstein-Barr virus (EBV), and human papillomavirus (HPV) types 2, 6, 16 and 18. The specific activities of viral DNA probes obtained by nick--translation ranged from 10(7) to 10(8) cpm/micrograms DNA. By Southern blot hybridization with an estimated sensitivity of 10 pg virus DNA which corresponded to 0.05 virus genome equivalents per cell we failed to detect any virus DNA in the biopsy material tested.
Keywords: Cytomegalovirus; Papillomaviridae; Nucleic Acid Hybridization; DNA, Viral; hybridizace nukleových kyselin; DNA virů; Herpesvirus 4, Human; lidé; virus Epsteinův-Barrové; adenom; Adenocarcinoma; Colonic Neoplasms; Humans; nádory tračníku; adenokarcinom; Adenoma